Studi Kelayakan Bisnis Dan Analisis SWOT UMKM Maharani Embroidery Handycraft - Yuniasari, Anggun Dwi (Jurnal Sekretaris dan Administrasi Bisnis, 2024)
A feasibility study on a business is needed which aims to see a picture of whether or not a business is feasible. Maharani Embroidery Handicraft is an MSMEs engaged in the industrial sector founded in 1996 and is located on Jl. D'wiga Regency A5.5, Sudimoro, Malang, East Java. Maharani Embroidery Handicraft sells various kinds of souvenirs, gifts, home decorations, and many more. This research aims to see whether Maharani Embroidery Handicraft is feasible or not. Every aspect that is said to be feasible must have a certain standard value. Assessment to determine business feasibility must be based on several aspects, namely technical aspects, socio-economic aspects, management aspects, marketing aspects, environmental aspects, legal aspects, and financial aspects. The methods used in this research are observation, interviews, and documentation. Maharani Embroidery Handicraft is said to be feasible in all aspects except the legal aspect becausethere are several incomplete files.The financial aspect shows that the calculation value above obtained the BEP value in units, namely 362 units, the calculation above obtained the BEP value in rupiah, which was Rp. 111.566,182. All calculation results in financial analysis also show that this business is feasible to run.